Screening of Refractive Disorders and Eye Health Awareness: Knowledge, Attitudes, and Behaviors of Elementary School Children in Semarang - Arnila Novitasari Saubig; Trilaksana Nugroho; Fifin Luthfia Rahmi; Andhika Guna Dharma (Faculty of Medicine, Diponegoro University, 2025)
Introduction: Refractive disorders are the leading cause of visual impairment. Uncorrected refractive errors in children can significantly impact their development, especially regarding education and psychosocial growth.Objective: This study aims to determine the prevalence of refractive disorders and to assess the knowledge, attitudes, and behaviors related to eye health among elementary school children at SemarangMethodology: This is a descriptive study involving 200 students from SDN Wonotingal Semarang as the sample. The study included eye examinations to identify refractive disorders in students and a questionnaire to collect data on their knowledge, attitudes, and behaviors regarding eye health. Data were collected through school-based eye screening and were analyzed using Microsoft Excel and SPSS version 26.Results: The prevalence of refractive disorders among children at SDN Wonotingal Semarang was 14%, with Astigmatism Myopia Compositus being the most common type of refractive disorder at 67.9%. Among the 28 children with refractive disorders, the majority were 11 years old (75%). Refractive disorders were more prevalent in females (64.29%) than males (35.71%). The questionnaire data revealed that a large number of children had poor knowledge about eye health (97.9%). However, most children exhibited good attitudes (79.5%) and behaviors (66.0%) regarding eye health.Conclusion: The prevalence of refractive disorders among children at SDN Wonotingal Semarang is 14%, with Astigmatism Myopia Compositus being the most common type. A significant number of children still have poor knowledge about eye health.